Injuries in male soccer players: team risk analysis - Inklaar, H.; Bol, E.; Schmikli, S. L.; Mosterd, W. L. (International Journal of Sports Medicine, 1996)
Selection may be responsible for different characteristics of subgroups (teams) of soccer players resulting in different risks of injury and different injury patterns. In the present study injury rates of teams were analysed with respect to the factors age and level of play. In two Dutch non-professional soccer clubs 477 male players, active in teams of different age groups and at different levels of play, were prospectively followed during the second half of the 1986/1987 competitive season. Teams in the 17/18 years age group showed the highest incidence of injury per 1000 players hours in games. At a high level of play teams have a significantly (p < 0.01) higher risk of injury than teams at a low level of play. This difference is noticed within every age group with exception of the 15/16 years age group. At a high level of play teams of senior players have significantly (p < 0.005) more prevalent injuries than teams of junior players. Senior players, active at a high level of play, have significantly (p < 0.05) more overuse injuries than senior players of a low level of play. At a high level of play significantly (p < 0.05) more upper leg injuries are reported. In the total population of soccer players relatively more sprains are located in the ankle joint and relatively more strains are located on the upper leg. It is concluded that prevention of soccer injuries primarily should be aimed at teams and their environment and not at the individual soccer player.